Tracing Poverty from Within: Household Drivers in High-Poverty Sumatera - Eka Dewi Anggraini; Ririn Nopiah (Universitas Bengkulu, 2026)
Poverty is a fundamental phenomenon in various countries, especially in developing nations. Solutions to eradicate poverty tend to be difficult and complex due to the multitude of factors influencing it. Poverty issues are not only affected by macro-level factors such as economic growth and others, but also by micro-level aspects. Bengkulu Province ranks among the three poorest regions on the island of Sumatra. This study identifies poor households in Bengkulu Province using a micro-level (household) approach. The methodology employed in this research utilizes household-level data from the National Socio-Economic Survey (SUSENAS) for Bengkulu Province during the 2020–2022 survey waves. The analytical methods used are logistic regression and multiple linear regression. The research findings indicate that health insurance ownership, the educational attainment of the household head, employment sector, credit recipient status, asset ownership, access to electricity, and Information Technology skills have a significant effect in reducing household poverty. The findings are expected to inform policymakers in designing more effective and efficient strategies and government programs tailored to alleviate poverty. Keywords: Poverty, Socioeconomic, Household, Bengkulu, SUSENAS Abstrak Kemiskinan merupakan fenomena mendasar di berbagai negara, terutama di negara berkembang. Solusi untuk memberantas kemiskinan cenderung sulit dan kompleks karena banyaknya faktor yang mempengaruhinya. Masalah kemiskinan tidak hanya dipengaruhi oleh faktor makro seperti pertumbuhan ekonomi dan lainnya, tetapi juga oleh aspek mikro. Provinsi Bengkulu termasuk di antara tiga wilayah termiskin di pulau Sumatera. Studi ini mengidentifikasi rumah tangga miskin di Provinsi Bengkulu menggunakan pendekatan mikro (rumah tangga). Metodologi yang digunakan dalam penelitian ini memanfaatkan data tingkat rumah tangga dari Survei Sosial Ekonomi Nasional (SUSENAS) untuk Provinsi Bengkulu selama gelombang survei 2020–2022. Metode analitis yang digunakan adalah regresi logistik dan regresi linier berganda. Temuan penelitian menunjukkan bahwa kepemilikan asuransi kesehatan, tingkat pendidikan kepala rumah tangga, sektor pekerjaan, status penerima kredit, kepemilikan aset, akses listrik, dan keterampilan Teknologi Informasi memiliki pengaruh signifikan dalam mengurangi kemiskinan rumah tangga. Temuan ini diharapkan dapat memberikan informasi kepada pembuat kebijakan dalam merancang strategi dan program pemerintah yang lebih efektif dan efisien yang disesuaikan untuk mengurangi kemiskinan.Kata Kunci: Kemiskinan, Sosial Ekonomi, Rumah Tangga Bengkulu, SUSENAS5